Efforts of the United Arab Emirates in Developing and Sustainability of the Arabic Language: Descriptive Analytical Study - Mohamed Abo Elnour Abdel Mawla, Mostafa; Al-Thunaibat, Fayz; Ayada Ayoub Alkubaisy, Amer (International Journal of Psychosocial Rehabilitation, 2020)
This research discusses the most important efforts made by the United Arab Emirates to serve the Arabic language and develop it and impose its sustainability locally and globally, because the Arabic language is the language of identity and the language of religion and the language of our Arab and Islamic civilization, and because of its delay in use and ignorance of its children, whether in educational institutions or the media in particular Satellite channels that boast - dearly - their dialects, so the UAE has made many efforts and initiatives at various levels, in social, educational, media and cultural institutions, as well as local and global; so this research was monitoring the most important of these Initiatives and their most important effects, as they have a major role in developing the basic skills of the Arabic language (listening - speaking - reading - writing). The study relied on the descriptive analytical approach by describing the most important of these efforts and analyzing the most important effects on them inside and outside the country.